IMPLEMENTASI KEBIJAKAN WAJIB BELAJAR 12 TAHUN DI KOTA CILEGON - Neneng Ratnanengsih; Maria Greissela; Hafijatu Zakiyah; Pingkan; Mila Rahmawati (Cahaya Ilmu Bangsa, 2024)
Cilegon City is one of the cities in Banten Province that implements the 12-Year Compulsory Education Policy. This policy is a continuation of the 9-Year Compulsory Education Program. Previously with the aim to maintain the success of the previous program and prepare Indonesia's golden generation in 2045. This research uses qualitative methods with field observation, interviews, and document collection as data collection techniques. Policy analysis is carried out using the Policy Implementation model according to Grindle which includes aspects of policy content and implementation context. The results showed that the Cilegon City Government is committed to supporting this policy by issuing an innovative program